2018
DOI: 10.1007/s10653-018-0188-7
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) in agricultural soils from Ningde, China: levels, sources, and human health risk assessment

Abstract: Soil-bound polycyclic aromatic hydrocarbons (PAHs) in farmland are critical to human health. The level, composition, source, and cancer risk of sixteen PAHs in agricultural soil from Ningde, China, were investigated. The results indicated that the total concentrations of 16 PAHs ranged from 77.3 to 1188 ng g, with a mean value of 406 ng g. Five-ring PAHs were found to have the highest concentrations (148 ± 133 ng g), followed by four-ring (120 ± 101 ng g), three-ring (61.9 ± 54.2 ng g), six-ring (44.6 ± 61.0 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…The World Health Organization (WHO) has reported that the ambient air pollution accounts for an annual death of about 4.2 million in 2016 by various chronic respiratory diseases [1]. Especially the Southeast Asia region, such as China and Korea, suffers a lot from the severe pollution caused by the airborne particles that consist of a mixture of fine dust, liquid mist, volatile organic compounds and possibly microbials [2,3,4,5]. The health risks associated with the airborne particles become serious for the particle size less than 2.5 µm, as such fine matters can even reach the bloodstream [3].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) has reported that the ambient air pollution accounts for an annual death of about 4.2 million in 2016 by various chronic respiratory diseases [1]. Especially the Southeast Asia region, such as China and Korea, suffers a lot from the severe pollution caused by the airborne particles that consist of a mixture of fine dust, liquid mist, volatile organic compounds and possibly microbials [2,3,4,5]. The health risks associated with the airborne particles become serious for the particle size less than 2.5 µm, as such fine matters can even reach the bloodstream [3].…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter (PM), consisting of solid particles, liquid aerosol, and gas and vapor compounds [1,2,3], is often classified by its aerodynamic diameter. PM 2.5, of which aerodynamic diameter ≤2.5 µm, is particularly reported as a serious threat to human health by the World Health Organization [4], because such an extremely small PM can be inhaled through respiratory organs, and then, circulated in the human body through blood vessels, potentially causing serious health problems [5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, factor 1 was marked as related to petroleum sources. ANT, PHE, and FLU, which are believed to be the tracers of wood/grass burning, dominated factor 2, which accounted for 18.75% of the total PAHs [33][34][35][36][37]. Hence, factor 2 was identified as originating from burning of biomass.…”
Section: Source Analysis Of Pahsmentioning
confidence: 99%